Synthesis of bis[(4,10-diaza-4,10-ditosyl-benzo-12-Crown-4) 4'-yl] diaminoglyoxime and its complexes - Avciata, U; Demirhan, N; Teker, M (KLUWER ACADEMIC PUBL, 1996)
A new macrocyclic ligand (HL) has been synthesised by reaction of 4'-amino-4, 10-diaza-4, 10-ditosyl-benzo-12-crown-4 with 1, 2-dichloroethanedial-dioxime. Protonation constants of the ligand and overall formation constants have been calculated from potentiometric data using the program TITFIT. Both amino and hydroxyimino groups provide donor atoms together with hydroxyl ions at higher pH values. The order of formation constants of the mononuclear complexes are U(VI)O-2 > Cu(II) > Ni(II) = Co(II) > Cd(II).
Keywords: crown ethers; preparation; protonation constants; formation constants; COBALT(II); COPPER(II); NICKEL(II); URANYL(VI); MACROCYCLE; Chemistry; Crystallography